2000
DOI: 10.1159/000012138
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB Genotypes in Japanese Patients with Renal Cell Carcinoma

Abstract: Objectives: Several clinical features, such as the spontaneous regression of some renal cell carcinoma (RCC) metastases after nephrectomy, suggest immune involvement in tumor destruction. Patients and Methods: We investigated the role of genetic variation at the HLA class II loci in RCC by analyzing the HLA-DR antigen and HLA-DRB1, DRB3, DRB4 and DRB5 alleles in 55 patients using the polymerase chain rection. Results: No statistically significant differences were observed in the frequency of the HLA-DR antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…While the most common alleles of DRB3/4/5 were DRB3*02:02 and DRB5*01:01 in Ningxia province located in the north of China (Liu & Liu, 2004), and DRB4*01:01 and DRB3*02:02 were the most common alleles in Hunan province located in the southeast of China (Wang et al., 2005). Other reports showed DRB4*01:03 and DRB3*02:02 were the most common alleles in population of Korea (Song et al., 2002), DRB4*01:01 and DRB3*02:02 were the most common alleles in Japanese (Kojima et al., 2000). However, HLA‐DRB4*01:01 and HLA‐DRB4*01:03 were the most common in the native Americans (Barquera et al., 2020), but HLA‐DRB4*01:03:01 and HLA‐DRB3*01:01:02 were common in European Americans and Mexicans (Creary et al., 2019; González‐Quezada et al., 2019 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While the most common alleles of DRB3/4/5 were DRB3*02:02 and DRB5*01:01 in Ningxia province located in the north of China (Liu & Liu, 2004), and DRB4*01:01 and DRB3*02:02 were the most common alleles in Hunan province located in the southeast of China (Wang et al., 2005). Other reports showed DRB4*01:03 and DRB3*02:02 were the most common alleles in population of Korea (Song et al., 2002), DRB4*01:01 and DRB3*02:02 were the most common alleles in Japanese (Kojima et al., 2000). However, HLA‐DRB4*01:01 and HLA‐DRB4*01:03 were the most common in the native Americans (Barquera et al., 2020), but HLA‐DRB4*01:03:01 and HLA‐DRB3*01:01:02 were common in European Americans and Mexicans (Creary et al., 2019; González‐Quezada et al., 2019 ).…”
Section: Discussionmentioning
confidence: 90%
“…However, compared with the two-field resolution data previously reported, some HLA alleles were further divided. For example, previously the most common alleles in Japanese (Kojima et al, 2000). However, HLA-DRB4*01:01 and HLA-DRB4*01:03 were the most common in the native Americans (Barquera et al, 2020), but HLA-DRB4*01:03:01 and HLA-DRB3*01:01:02 were common in European Americans and Mexicans (Creary et al, 2019;González-Quezada et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…DRB1*1501 has also shown strong associations with several diseases such as paroxysmal nocturnal hemoglobinuria (47), multiple sclerosis (48) and human papillomavirus type 16-related cervical cancer (49). In addition, associations between DRB1*1202 and renal cell carcinoma (50), DRB1*1302 and postherpetic neuralgia (51) or nonobstructive azoospermia (52), and DRB1*1405 and prostate cancer (53) have been reported in the Japanese population. Given the central role of BTNL2 products in the immune response (54), BTNL2 might be an attractive candidate gene for the susceptibility to these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, class II molecules present exogenous antigens to helper T lymphocytes and induce humoral immune responses. Evidences suggest that MHC class II genes may play an important role in developing the risk of different tumors including cutaneous T cell lymphoma [26], renal cell carcinoma [11], breast cancer [19, 27], melanoma [13], acute leukemia [14], cervical cancer [15], and colorectal carcinoma [16] and any changes to the molecular structure of this class could be related to these neoplasms. Nevertheless, it is unclear that MHC II alleles in themselves have a causative effect on the development of tumors or whether they are the markers showing indirect association with the causative genes located in their vicinity and are in linkage disequilibrium with them.…”
Section: Discussionmentioning
confidence: 99%
“…A strong association between MHC class II alleles and risk of developing different types of tumors has been reported in humans. Previous studies demonstrated the role of the HLA-DRB1 locus in genetic susceptibility to colorectal carcinoma, cervical cancer, acute leukemia, melanoma, renal cell carcinoma, and breast cancer [1116]. Several other studies conducted in humans have also showed that some HLA-DRB1 genotypes may increase or decrease the risk of breast cancer [12, 1719].…”
Section: Introductionmentioning
confidence: 99%